1999
DOI: 10.2170/jjphysiol.49.467
|View full text |Cite
|
Sign up to set email alerts
|

Central Control Mechanisms of Circulation in the Medulla Oblongata by Nitric Oxide.

Abstract: reported that the relaxation of isolated rabbit aorta and other arteries induced by acetylcholine and other agonists for muscarinic receptors was dependent on the presence of endothelial cells within the preparations [2]. After removal of these cells, acetylcholine could no longer induce relaxation. Endothelium-dependent relaxation by acetylcholine results from the release of a diffusable relaxing substance, which was later termed endothelium-dependent relaxing factor (EDRF) [3,4]. It has been shown that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 107 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…It was shown that it takes part in many processes in the central nervous system like synaptic plasticity in the hippocampus (Krushkov et al 1996), claustral functioning (Hinova-Palova et al 1997), eye movements (Moreno-Lopez et al 1996, thalamic functioning (Krushkov et al 1996), blood pressure control (Maeda et al 1999), inferior colliculus functioning , vestibular complex functioning (Papantchev et al, , 2006 and so forth. NO is synthesized by the enzyme Nitric oxide synthase (NOS).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that it takes part in many processes in the central nervous system like synaptic plasticity in the hippocampus (Krushkov et al 1996), claustral functioning (Hinova-Palova et al 1997), eye movements (Moreno-Lopez et al 1996, thalamic functioning (Krushkov et al 1996), blood pressure control (Maeda et al 1999), inferior colliculus functioning , vestibular complex functioning (Papantchev et al, , 2006 and so forth. NO is synthesized by the enzyme Nitric oxide synthase (NOS).…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnol. Biochem., 72 (9), [2476][2477][2478][2479][2480]2008 Communication Dawley rats (250-300 g) were group-housed (three per cage) and acclimatized under laboratory conditions (temperature, [22][23][24] C; humidity, 60 AE 10%; fixed light-dark cycle, lights on 0800 to 2000 H) for 10 d prior to the feeding experiment. Food (MF, Oriental Yeast Company, Tokyo) and water were given ad libitium.…”
mentioning
confidence: 99%
“…For example, forced swimming, hemorrhage, and restraint stress activate both A1 and A2, 20) whereas conditioned fear/emotional stress and cholecystokinin, an aversive agent, preferentially activate A2. 21) Nevertheless, modest caudal activation of VLM is associated with a rise in blood pressure, 22) due to the stress experienced by the rats during handling.…”
mentioning
confidence: 99%